Pentoxifylline versus Steroid Therapy for Idiopathic Sudden Sensorineural Hearing Loss with Diabetes - Lan, Wei-Che (J Int Adv Otol, 2018)
OBJECTIVES: To compare the efficacy of pentoxifylline with that of conventional steroid therapy in diabetic patients with idiopathic sudden sensorineural hearing loss (ISSNHL) and to compare blood sugar levels during hospitalization. MATERIALS AND METHODS: Medical charts were retrospectively reviewed for all diabetic patients admitted to one institution for ISSNHL between 2000 and 2015. We analyzed 298 cases; 50 patients received pulse steroid treatment (steroid group) and 248 received intravenous administration of pentoxifylline only (pentoxifylline group). Hearing change was evaluated by comparing the initial hearing tests with follow-up hearing tests for up to 3 months. Blood sugar levels were also compared between the 2 groups. RESULTS: At 3 months post-treatment, the degree of hearing recovery was similar between the 2 groups. The pure-tone average was improved from baseline by 17.9±21.2 dB in the steroid group and 18.9±20.7 dB in the pentoxifylline group (p=0.776); hearing recovery rates were also similar (40% vs 39.1%; p=0.826). During hospitalization, average fasting blood sugar levels were higher (203.9±92.0 vs 174.4±54.8 mg/dL; p=0.033) and acute hyperglycemia was more common (48.0% vs 33.1%; p=0.044) with steroid versus pentoxifylline treatment. CONCLUSION: Hearing recovery rates did not significantly differ between steroid and pentoxifylline treatment in diabetic patients with ISSNHL, but pentoxifylline appeared to be associated with better blood sugar control.